Pro-Inflammatory Cytokines at Ultra-Low Dose Exert Anti-Inflammatory Effect In Vitro: A Possible Mode of Action Involving Sub-Micron Particles? - Ilaria Floris; Thorsten Rose; Juan Antonio Collado Rojas; Kurt Appel; Camille Roesch; Beatrice Lejeune (SAGE Publishing, 2020)
Tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) are pro-inflammatory cytokines involved in acute and chronic inflammatory diseases. Indeed, immunotherapy blocking these 2 cytokines has been developed. Micro-immunotherapy (MI) also uses ultra-low doses (ULD) of pro-inflammatory cytokines, impregnated on lactose-sucrose pillules, to counteract their overexpression. The study has been conducted with 2 objectives: examine the anti-inflammatory effect in vitro and the capacity of 2 unitary medicines, TNF-α (27 CH) and IL-1β (27 CH), to reduce the secretion of TNF-α in human primary monocytes and THP-1 cells differentiated with phorbol-12-myristate-13-acetate, after lipopolysaccharide (LPS) exposure; then, investigate the presence of particles possibly containing starting materials using tunable resistive pulse sensing technique. The results show that the unitary medicines, tested at 3 pillules concentrations (5.5, 11 and 22 mM), have reduced the secretion of TNF-α in both models by about 10−20% vs. vehicle control, depending on concentration. In this exploratory study, particles (150−1000 nm) have been detected in MI ULD-impregnated pillules and a hypothesis for MI medicines mode of action has been proposed. Conscious that more evaluations are necessary, authors are cautious in the conclusions because the findings described in the study are still limited, and future investigations may lead to different hypothesis.